Sodium-calcium exchanger and R-type Ca2+ channels mediate spontaneous [Ca2+]i oscillations in magnocellular neurones of the rat supraoptic nucleus. Issue 6 (June 2016) - Kortus, Stepan; Srinivasan, Chinnapaiyan; Forostyak, Oksana; Zapotocky, Martin; Ueta, Yoichi; Sykova, Eva; Chvatal, Alexandr; Verkhratsky, Alexei; Dayanithi, Govindan
Graphical abstract: Schematic diagram shows the possible Ca 2+ transport mechanisms with highlights (red) of those that were identified as essential for [Ca 2+ ]i oscillations in the magnocellular neurones of the supraoptic nucleus. Highlights: Mechanisms of spontaneous [Ca 2+ ]i oscillations observed in the supraoptic nucleus vasopressin and oxytocin neurones have been found. Extracellular Ca 2+ is essential for oscillations whereas targeting intracellular Ca 2+ stores did not prevent cells from oscillations. Oscillations are mainly regulated by the high-voltage-dependent Ca 2+ channels dominated by R-type channel, the Na + /Ca 2+ exchanger in the reverse mode, and the plasmatic-Ca 2+ -ATPase pump. Oscillations may need changes in membrane potential but do not require action potentials. The mitochondrial role in the oscillations is less clear. Abstract: Isolated supraoptic neurones generate spontaneous [Ca 2+ ]i oscillations in isolated conditions. Here we report in depth analysis of the contribution of plasmalemmal ion channels (Ca 2+, Na + ), Na + /Ca 2+ exchanger (NCX), intracellular Ca 2+ release channels (InsP3 Rs and RyRs), Ca 2+ storage organelles, plasma membrane Ca 2+ pump and intracellular signal transduction cascades into spontaneous Ca 2+ activity. While removal of extracellular Ca 2+ or incubation with non-specific voltage-gated Ca 2+ channel (VGCC) blocker Cd 2+ suppressed the oscillations, neither Ni 2+ nor TTA-P2, the T-type VGCC blockers, had an effect. Inhibitors of VGCC nicardipine, ω-conotoxin GVIA, ω-conotoxin MVIIC, ω-agatoxin IVA (for L-, N-, P and P/Q-type channels, respectively) did not affect [Ca 2+ ]i oscillations. In contrast, a specific R-type VGCC blocker SNX-482 attenuated [Ca 2+ ]i oscillations. Incubation with TTX had no effect, whereas removal of the extracellular Na + or application of an inhibitor of the reverse operation mode of Na + /Ca 2+ exchanger KB-R7943 blocked the oscillations. The mitochondrial uncoupler CCCP irreversibly blocked spontaneous [Ca 2+ ]i activity. Exposure of neurones to Ca 2+ mobilisers (thapsigargin, cyclopiazonic acid, caffeine and ryanodine); 4-aminopyridine (A-type K + current blocker); phospholipase C and adenylyl cyclase pathways blockers U-73122, Rp-cAMP, SQ-22536 and H-89 had no effect. Oscillations were blocked by GABA, but not by glutamate, apamin or dynorphin. In conclusion, spontaneous oscillations in magnocellular neurones are mediated by a concerted action of R-type Ca 2+ channels and the NCX fluctuating between forward and reverse modes.